Proposição de um canteiro de obra para uma edificação de grande porte na cidade de Caraúbas-RN - Cavalcante, Carlos Heitor Targino Dantas (Universidade Federal Rural do Semi-Árido, 2018)
The construction industry is an industry that has always been looking for improvements to its work environment. One of these improvements is to think about how the planning of the support elements for the progress of the work will be carried out before starting the construction itself, ie, to think logistically about how the ideal positions of the sites will be used to support the progress of the work and organize them in the area of construction. A job with a disorganized construction site could lead to more work, an unsafe flow for the workers, a greater waste of time and, as a consequence, generate more labor costs. With this, today's civil engineers must seek efficient and well-engineered solutions strategically so that the construction environment is sound, safe, comfortable and has a good flow of operation. This work had as objective to dimension a construction site in a logistic way, where in the same it was made a proposal of a layout of a large postage in the city of Caraúbas-RN. In the first step, a bibliographic survey was carried out exploratoryly on research related to the site. In the second stage a site was chosen that has size for a large construction and that at the same time has conditions to be made a bed that includes most of the elements that compose it. In the third stage the layout of the construction site was created and planned meeting the specifications of the NR-18. In the fourth stage an analysis of the logistic of the same was made, detailing the elements of the operational areas and living area, based on a methodology of the author "Souza et al.", Which speaks of the general recommendations regarding the location and size of the elements of the construction site. Finally, it was designed a nursery with a living area for 120 employees that include changing rooms, bathrooms, dining rooms, kitchen, laundry, accommodation, recreation area, training room / literacy and outpatient clinic. In the elements linked to production was inserted: mortar and concrete center, frame center, formwork center, pre-assembly center of facilities (miter and pre-molded). In the elements of production support was filled by: tool storage, warehouse of contractors, 4 stocks for sand and gravel, cement and lime stock, pipe stock, connections and metal stock, window stock, steel stock and stock from plywood to plywood. In the elements of technical / administrative support: engineer's office, technician's room, Outsourced room, master-builder's room and supervisors, administrative / inspection office, reception / guardhouse and point chrome. There are also other elements, which are formed by: "stand" sales, gates and siding.
Monografia
Keywords: Dimensionar; Proposição; Canteiro de obras; Análise da logística; ENGENHARIAS::ENGENHARIA CIVIL